Australian consumers' attitudes to packaged fresh meat products with added microbial bioprotective cultures for shelf-life extension. (April 2023) - Xu, Michelle M.; Kaur, Mandeep; Pillidge, Christopher J.; Torley, Peter J.
Abstract: The application of food-grade microbial cultures to fresh meat products is a promising natural approach for meat shelf-life extension. However, before its adoption into commercial practice, it is essential to understand consumers' attitudes to this approach and the resulting marketed products. This study investigated Australian consumers' willingness to purchase and consume packaged fresh meat products with added microbial cultures for shelf-life extension. A national online survey of over 800 respondents was conducted. Results indicated that most Australian consumers would be willing to buy and eat such products, with 17.8% of respondents less likely to buy and 11.1% unwilling to eat these products. Respondents' purchasing and consumption decisions were influenced by demographic factors, their food and meat shopping and consumption behaviors, and the value, taste, and type of the meat product. Consumer acceptance may be improved by increasing their awareness of the potential use of microbial cultures as natural antimicrobials for food shelf-life extension. Graphical abstract: Unlabelled Image Highlights: Consumer acceptance of fresh meat with added microbial cultures was investigated Most Australian consumers would buy and eat these products Buying and eating decisions were influenced by age, gender, and employment status Various food and meat shopping and consumption behaviors also had impacts